Strontium aluminate compound as road line materials application - Vikneswaran Munikanan,; Ng, Choy Peng; Muhamad Azani Yahya,; Mohammed Alias Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Road line marking are used as a mean of controlling traffic and road user safety. It is very significant on any roads and intersections as they promote road safety. They highlight a harmonious flow of traffic along guided paths of travel. The objectives of this study are to investigate the properties of road line materials and examine the illuminance properties of glow in the dark powder applied in road marking materials. The use of photoluminescent glow-in-the-dark material was tested in the lab for its suitability (luminosity and the glow duration). The methods involved are selection of suitable type of glow in the dark materials, selection of optimum mixing ratio of the glow in the dark powder with thermoplastic powder, and finally analyzed for the properties of the type of the material chosen. The fine granular strontium aluminate compound, SrAl2O4 was selected as the most suitable type of glow in the dark material. Based on the laboratory analysis, the optimum ratio of the glow in the dark material to be used with thermoplastic powder is 55% of total mix volume. The average visible light emission period is in acceptable range of 20 m. This is a suitable distance to implement the road line because of the high visibility on the road during dark or night.